Regional geoid determination in Tierra del Fuego including GPS levelling - Del Cogliano, Daniel Héctor (2007)
A regional geoid model for the Argentine part of the Isla Grande de Tierra del Fuego, established in previous works on the basis of GPS levelling, suffers a lack of observation data in the remote south-western investigation area. In order to improve the data distribution in this region, the mean lake level of Lago Fagnano has been regarded as a natural indicator for the local geoid. Using a GPS buoy and pressure tide gauges, a method to determine the mean lake surface topography with respect to the ellipsoid has been developed. It is shown that the obtained lake level geometry is essentially controlled by the regional gravity field. The derived information on the mean lake level has been included in the geoid model, which results in a more detailed and plausible representation of the regional geoid.